Response of rhizobium inoculation on growth and productivity of fenugreek (Trigonella foenum-greacum) under salt stress condition - KUMARI, RENU; SINGH, ALKA; KUMAR, P; KUMAR, NARENDRA (The Indian Journal of Agricultural Sciences, 2016)
Soil salinity is a major restriction to crop production in many areas of the world. Crops growing in salt-affected soils may suffer from many physiological stress and ion toxicity which then lead to reduced growth and productivity. The present study was under taken on the effect of salinity and rhizobium inoculated seeds on plant growth and productivity of fenugreek (Trigonella foenum-greacum L.) cultivars (NDM-17 and Pusa Kasauri). The pot experiment was conducted in completely randomized block design with three replicates. Two sets of pot trails were maintained in which one inoculated with effective rhizobium strain (Rhizobium meliloti) while other set was uninoculated. Both sets were irrigated with saline water of different electrical conductivities (0, 3, 6, 7, 10, 12 and 14 dS/m). Salinity stress registered the highest detrimental effects on growth and productivity. Present findings revealed that the inoculated seeds with effective rhizobium strain minimized the deleterious effect of salinity at all levels. The maximum growth and productivity was found in NDM-17 in both sets inoculated and uninoculated with rhizobium as compared to Pusa Kasauri.